Maximal exercise capacity in patients with obstructive sleep apnoea syndrome: a systematic review and meta-analysis. Issue 6 (28th June 2018) - Mendelson, Monique; Marillier, Mathieu; Bailly, Sébastien; Flore, Patrice; Borel, Jean-Christian; Vivodtzev, Isabelle; Doutreleau, Stéphane; Tamisier, Renaud; Pépin, Jean-Louis; Verges, Samuel
Maximal aerobic capacity is a strong health predictor and peak oxygen consumption ( V ′O2 peak ) is considered a reflection of total body health. No systematic reviews or meta-analyses to date have synthesised the existing data regarding V ′O2 peak in patients with obstructive sleep apnoea (OSA). A systematic review of English and French articles using PubMed/MEDLINE and Embase included studies assessing V ′O2 peak in OSA patients either in mL·kg −1 ·min −1 compared with controls or in % predicted. Two independent reviewers analysed the studies, extracted the data and assessed the quality of evidence. Mean V ′O2 peak expressed in mL·kg −1 ·min −1 was significantly lower in patients with OSA than in controls (mean difference −2.7 mL·kg −1 ·min −1 ; p<0.001; n=850). This reduction in V ′O2 peak was found to be larger in non-obese patients (body mass index <30 kg·m −2 ). Mean V ′O2 peak % pred was 89.9% in OSA patients (n=643). OSA patients have reduced maximal aerobic capacity, which can be associated with increased cardiovascular risks and reduced survival in certain patient subgroups. Maximal exercise testing can be useful to characterise functional limitation and to evaluate health status in OSA patients. Maximal exercise capacity as a reflection of total body health is reduced in patients with obstructive sleep apnoea http://ow.ly/EdaD30jAE7k